Adipose-derived mesenchymal stem cells reduce MMP-1 expression in UV-irradiated human dermal fibroblasts: therapeutic potential in skin wrinkling. Issue 6 (3rd June 2015) - Son, Woo-Chan; Yun, Jun-Won; Kim, Bae-Hwan
Abstract: Adipose-derived mesenchymal stem cells (AdMSCs) have been reported to have therapeutic benefit in skin. The aim of this study was to examine the effects of AdMSCs in UV-irradiated human dermal fibroblasts (HDFs) for therapeutic potential in skin wrinkling. UV irradiation, a model naturally mimic skin wrinkle formation, is known to increase matrix metalloproteinase-1 (MMP-1), making MMP-1 a target for skin photoaging. Our findings identified that AdMSCs reduce MMP-1 level in UV-irradiated HDFs and increase type 1 procollagen in HDFs. A dose-dependent increase in type 1 procollagen was confirmed by AdMSC-conditioned medium. Importantly, our current findings showing the effects of AdMSCs on the induction of MMP-1 in UV-radiated HDFs and the expression of collagen in HDFs can provide an evidence of relationship between MMP-1 and procollagen production for the protection against wrinkle formation. Collectively, AdMSCs may contribute to anti-wrinkle effects in skin but further experiments are needed to identify the mechanism. Abstract : : Characterization of HDFs and AdMSCs. (A) Morphology of HDFs (x100), (B) Morphology of ADSC (x100), (C) Morphology of co-culture status of HDF and ADSC (x40).